Inventarization and Identification of Fish in the Parit Belanda River Rumbai Pesisir District Pekanbaru, Riau - Gusriyeni Dwi Mandelasari; Efawani '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Parit Belanda River is one of Siak River tributaries and it is inhabited by various species of fish. To understand the type of fish living in that river, a study has been conducted on November-December 2015. Samplings were conducted 2 weekly, in 3 stations; in the upstream (ST I), middle (ST II) and downstream (ST III) of the river. Results shown that there were 129 fishes captured and they are belonged to 27 species. Seven species (26%) are categorized as ornamental fish (Esomus metallicus, Rasbora chrysotaenia, Dermogenys pusilla, Poecelia reticulata, Betta waseri, Trichogaster leerii and Trichopsis vittata). Other 7 species (26%) are edible fish (Thynnichthys polylepis, Channa lucius, Channa striata, Oreochromis niloticus, Mystus nemurus, Mystus nigriceps and Monopterus albus). While 13 other species can be classified as ornamental-edible fish (Cyclocheilichtys apogon, Hampala macrolepidota, Labiobarbus leptochilus, Osteochilus hasselti, Puntius binotatus, Puntius bulu, Oxyeleotris marmorata, Anabas testudineus, Trichogaster pectoralis, Trichogaster trichopterus, Helostoma temminckii, Osphronemus goramy and Pterygoplichthys pardalis).Keyword: ornamental fish , edible fish, ornamental-edible fish , Parit Belanda River Rumbai Pesisir District Pekanbaru, Riau